2014
DOI: 10.3109/13506129.2014.900487
|View full text |Cite
|
Sign up to set email alerts
|

In silicoanalysis ofTTRgene (coding and non-coding regions, and interactive network) and its implications in transthyretin-related amyloidosis

Abstract: Our data provided new insights into the pathogenesis of TTR-related amyloidosis that, if they were to be confirmed through experimental investigations, could significantly improve our understanding of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Although these ancestry differences are likely biased by the rare disease prevalence and the variability of the clinical practice guidelines across different countries, the inter-population diversity of the molecular mechanisms involved in the genotype-phenotype correlation surely plays an important role in the clinical presentation observed in patients with different ancestry backgrounds. Our previous investigations indicated that TTR non-coding regions are affected by human population diversity with potential consequences on gene regulation [12, 14, 15]. Our hypothesis is in agreement with many studies about the regulatory role of non-coding variation on gene expression and other gene functions [24, 25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although these ancestry differences are likely biased by the rare disease prevalence and the variability of the clinical practice guidelines across different countries, the inter-population diversity of the molecular mechanisms involved in the genotype-phenotype correlation surely plays an important role in the clinical presentation observed in patients with different ancestry backgrounds. Our previous investigations indicated that TTR non-coding regions are affected by human population diversity with potential consequences on gene regulation [12, 14, 15]. Our hypothesis is in agreement with many studies about the regulatory role of non-coding variation on gene expression and other gene functions [24, 25].…”
Section: Discussionsupporting
confidence: 92%
“…We observed an enrichment for non-coding regulatory variants located in heart-related transcription-factor binding sites in African populations, suggesting a contribution to the cardiomyopathy observed in patients of African ancestry [12]. We also investigated the haplotype structures of Val30Met and Val122Ile [rs76992529, c.424G > A, p.Val142Ile] mutations, observing in both cases independent haplotypes carrying the same disease-causing mutation [14, 15]. Non-coding variation regulates genome functions, especially through its key role in transcriptional mechanisms across human tissues [16].…”
Section: Introductionmentioning
confidence: 99%
“…4,25 The re-sequencing analysis of the TTR gene (coding and noncoding regions) in Italian patients allowed us to deepen our previous finding on the role of non-coding TTR variations in the disease genotype-phenotype correlation. [15][16][17] Investigating the TTR haplotypic structure, we observed that the correlation between the Val30Met mutation and the ocular manifestation can be attributed to a specific Val30Met haplotype, which includes two regulatory non-coding variants. As also reported in genetic studies of different phenotypic traits, 38,39 the ocular manifestation in TTR amylodosis in our sample is due to a combination of the effects of a coding amylodogenic mutation and SNPs located in non-coding elements.…”
Section: Discussionmentioning
confidence: 99%
“…15 Then, we analyzed the haplotypes associated with the Val122Ile (rs76992529, c.424G4A, p.(Val142Ile)) and Val30Met mutations, and identified independent haplotypes for the same mutation, suggesting multiple mutational events and different origins for these disease-causing mutations. 16,17 As non-coding variants located in regulatory elements can affect gene expression, 18 we hypothesize that these variations influence the distribution and accumulation of TTR-derived fibrils across different tissues and organs, modulating consequently the disease phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Others have hypothesized that variation at transcription factor binding sites within populations resulting in different transcription levels presumably increased, resulting in increased serum TTR concentrations, could also be responsible for different degrees of clinical penetrance (Polimanti et al. ). While there are no available data regarding hepatic TTR transcription in different carriers of the same amyloidogenic allele, we think this unlikely since serum TTR concentrations tend to be lower rather than higher in carrier subjects even before there is detectable tissue deposition.…”
Section: Discussionmentioning
confidence: 99%